A nationwide population-based study on overall survival after meningioma surgery. (February 2021) - Champeaux-Depond, Charles; Weller, Joconde; Froelich, Sebastien; Resche-Rigon, Matthieu
Highlights: After meningioma surgery, overall survival at 5 and 10 years respectively were 92.6 % and 85 %. Survival is prolonged in women, younger adults and those with convexity and benign tumour. Those required additional treatment for uncontrolled disease are further at risk of death. Abstract: Background: There are very few nationwide studies on meningioma outcome, the most common primary intracranial tumour. Methods: We processed the French Système National des Données de Santé (SNDS) database using an algorithm combining the type of surgical procedure and the International Classification of Diseases to retrieve all cases of meningiomas operated between 2007 and 2017. A survival analysis was performed. Results: This nationwide study found 28 773 patients of which 75 % were female. Median age at surgery was 59 years, IQR[49–68]. Cranial convexity (24.4 %) and middle skull base (21.7 %) were the most common locations. 91.3 % of the tumours were benign and 2.6 % malignant.7.5 % of the patients underwent redo surgery, 9.1 % radiotherapy (RT) and 3.2 % stereotactic radiosurgery for recurrence. Median follow-up was 5.3 years 95 % CI [5.24–5.35]. 0.64 % of the patients died within a month of surgery and 2.1 % within a year. Overall survival (OS) rates at 5 and 10 years respectively were: 92.6 %, 95 %CI[92.3, 93] and 85 %, 95 %CI[84.3, 85.8]. In the multivariable analysis, female gender (HR = 0.64, 95 %CI[0.59, 0.69], p < 0.001), older age at surgery (HR= 1.07, 95 %CI[1.06, 1.07], p < 0.001), type 2 neurofibromatosis (HR= 3.89, 95 %CI[2.62, 5.76], p < 0.001), parasagittal (HR= 1.2, 95 %CI[1.05, 1.37], p = 0.00944) or falx cerebri location (HR= 1.18, 95 %CI[1.01, 1.37], p = 0.0343), atypical or (HR= 1.34, 95 %CI[1.15, 1.56], p < 0.001) malignant histology (HR= 2.34, 95 %CI[2.01, 2.73], p < 0.001), redo surgery (HR=1.81, 95 %CI[1.6, 2.04], p < 0.001), progressing meningioma (HR=1.34, 95 %CI[1.05, 1.71], p = 0.0175) or RT for recurrence (HR=2.17, 95 %CI[1.95, 2.4], p < 0.001) were established as independent prognostic factors of the OS. Conclusion: In this registry-based study, OS after meningioma surgery is good and is even better in women, younger adults and those with convexity and benign tumour. We also found that NF2 patients and those required redo surgery or additional treatment for uncontrolled meningioma disease are further at risk of death.